Lead Distribution on Marsilea crenata and Its Effect on Growth and Total Protein Content - Arry Y. Nurhayati; Yuda C Hariadi (UNEJ e-Proceeding, 2014)
The increasing risk of lead poisoning such as neuro-behavioral disorders and neurological damage; hypertension, brain and kidney damage; DNA and antioxidant defense system cell damage in developing countries due to the increase in lead contaminated environment. This research was aimed to investigate the effects of prolonged lead on protein levels in the Marsilea crenata plant. The plants have been used for generation by local farmers as a daily source of vegetables during crop growing season. The plants are also known as an exotic cuisine known as Semanggi Surabaya. Marsilea crenata were grown inside a glasshouse using a modified Hoagland solution in different levels of Pb. The growth, Pb content, and total protein content were then measured for eight weeks during exposure. The result has shown that the root of Marsilea crenata has the capability to absorb lead and translocate them inside its shoots and leaves, with the biggest amount were translocated to the younger leaves during one week of exposure and was then accumulated in the old leaves after longer exposures. Total protein content was higher on younger leaves than in older leaves, followed by shoot and then the root. The result has shown that with deep knowledge of Marsilea crenata it is possible of using it as a phytoremediator or as a source of food since the total protein was translocated on the edible part. Still, awareness is still needed since the plant may contain high levels of Pb with the existence of stress symptoms. It should be avoided to reduce the risk of lead poisoning. Keywords: Lead, Marsilea crenata, growth, protein